2020
DOI: 10.1097/ccm.0000000000004613
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Exchange: An Effective Rescue Therapy in Critically Ill Patients With Coronavirus Disease 2019 Infection

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(84 citation statements)
references
References 14 publications
4
75
0
1
Order By: Relevance
“…Increasing publications of case series and case reports from centers across the world have now described the efficacy of TPE in over 60 COVID-19 patients that did not respond to initial therapies, with the majority having been treated with corticosteroids. 185 -195 Nearly all describe similar positive physiologic and clinical responses temporally associated with initiation or completion of TPE. Further, 3 retrospective, observational cohort studies including a total of 74 patients treated with plasmapheresis have reported dramatic differences in both extubation and survival.…”
Section: Methylprednisolone and Covid-19mentioning
confidence: 99%
“…Increasing publications of case series and case reports from centers across the world have now described the efficacy of TPE in over 60 COVID-19 patients that did not respond to initial therapies, with the majority having been treated with corticosteroids. 185 -195 Nearly all describe similar positive physiologic and clinical responses temporally associated with initiation or completion of TPE. Further, 3 retrospective, observational cohort studies including a total of 74 patients treated with plasmapheresis have reported dramatic differences in both extubation and survival.…”
Section: Methylprednisolone and Covid-19mentioning
confidence: 99%
“…The patient was successfully weaned off mechanical ventilation but remained hospitalized. Fernandez et al 36 provided TPE to one COVID‐19 patient with pneumonia and APS, who then became stable for discharge. A number of neurologic conditions have been suspected to be associated with COVID‐19.…”
Section: Covid‐19 and Therapeutic Plasma Exchangementioning
confidence: 99%
“…In first case series plasma exchange was used to attenuate circulating cytokines and inflammatory mediators in critically ill patients with COVID-19. Case series from Barcelona and Heidelberg describe favorable effects on parameters of inflammation and clinical outcome[9, 10]. In a cohort in Oman, 11 critically ill patients underwent plasma exchange.…”
Section: Brief Reportmentioning
confidence: 99%